Guidelines for laboratory design : health and safely consideration / Louis Diberardinis ... [et al.]. - DiBerardinis, Louis J., 1947- (Wiley, 2001)
This volume provides design information related to specific health and safety issues that should be considered when planning new or renovated laboratories.